A formação continuada dos professores em um centro de educação infantil (CEI) do município de São Paulo - Olim, Michele Pimentel (2019)
Proposed as object of study the proposed continuing education undertaken in an early childhood Center of São Paulo. Using this object of study emerged some concerns that prompted and guided the development of this research: The continuing education as has been made of possible investigative position basic issues of teaching and educational practice? How to implement a collaborative training in CEI? What contributions the work with the pedagogical meetings can provide continuing training of teachers of a CEI? How to build a proposal of continuous formation of teachers who consider a collaborative perspective and research focused on reflections on the foundations of education and pedagogical practice through the work with classics of education? With the questions presented, delimited as general objective training space as locus of collective reflection on the fundamentals of teaching and your relationship with pedagogical practice. This formation occurs three times a week, in meetings with one hour of duration and during eight months of the school year. Specific objectives of the research are listed below: investigate, theoretically, if the continuing education that has been made provides investigative position of basic issues of teaching and pedagogical practice, build a proposal for collaborative training in CEI, reflect on the contributions of the work with pedagogical continuing training meetings of teachers of the CEI and see how the proposal of continuous formation of teachers in a collaborative perspective and research focused on a reflections in discussion of the relationship between the fundamentals of education and pedagogical practice through the work with classical education. Based on the presented objectives, the research developed had a qualitative approach, being of the research-training type. The following data collection instruments were used: (1) survey questionnaire regarding the training and professional data of the participants; (2) pedagogical groups; (3) individual written records. During the research-training meetings, the data produced through the tertúlias were recorded and then transcribed, for tabulation and analysis according to the categories of analysis, namely: teacher function, child and Maria Montessori concepts and formative experience. The subjects were forty-four teachers, who taught from Nursery I to Mini Group II, encompassing the age group from zero to three years old. he research will be based on the following authors: Lima (2002); Oliveira (2012); Domingues (2014); Nóvoa (1992); Schön (2000), Kuhlmann Jr. (2000); Alarcão (2001); Tardif (2014) and educational documents whose themes are related to collaborative training, early childhood education, pedagogical practices and teacher training. The main results can be: at the opportunity of trocarem information about seus anseios, medos and angústia and also opportunizaram reconnecimento of moments of joy and satisfaction ao longo of all to research, teachers passaram to auto avaliar, e moments of colaboração Participatory and investigative activities will come up in a school unit.